Analisis Pertumbuhan Ekonomi Dan Ketimpangan Pendapatan, Panel Data Enam Provinsi Di Pulau Jawa - Yosi Eka Putri; Erita Erita (Universitas Negeri Padang, 2019)
This study aims to analyze (1) the effect of regional fiscal autonomy degrees, tax and investment ratios on economic growth in Indonesia, (2) the effect of economic growth, labor productivity, investment and the Human Development Index (HDI) on income inequality in Java.The type of research is descriptive and associative research. The type of data is documentary data, the data source is panel data during 2013 - 2017 in six provinces in Java. This study uses simultaneous equation modeling tools with the Indirect Least Squared method ( ILS) Common Effect. Endogenous variables in the study are economic growth and income inequality. While the exogenous variables are regional fiscal autonomy, tax ratios, labor productivity, investment and the Human Development Index (HDI).The results of the study concluded that (1) the variables of regional fiscal autonomy, tax and investment ratios had a significant effect on economic growth in Java.. (2) Variable economic growth, labor productivity, investment and HDI significantly affect income inequality in Java. The policies that can be suggested are that efforts are needed to increase economic growth with the efforts of the central government together with regional governments to increase Regional Original Revenue (PAD) by optimizing regional potentials. Increasing the potential of this area will encourage the increase of PAD in each region will have an impact on the increasing degree of regional fiscal autonomy (ratio between PAD and Total Regional Revenue). Focus more on equity-oriented development not only on economic growth. Keywords: economic growth, income inequality